Influence of Different Rootstocks on Vine Growth, Bunch Yield, Quality, Chlorophyll Content and Photosynthetic Activity in Crimson Seedless Grapevine - Somkuwar, R. G.; Gobade, Nilima; Deshmukh, N. A.; Ramteke, S. D.; Kakade, Pradip; Karande, P. S. (International Journal of Bio-resource and Stress Management, 2025)
A field experiment was carried out from 2021 to 2024 at the ICAR-National Research Centre for Grapes, Pune, to assess the impact of four different rootstocks (110R, 140Ru, 1103P and Dogridge) on vine growth, bunch yield, quality, chlorophyll content and photosynthetic activity in Crimson Seedless grapevines. Growth parameters, including pruned biomass (0.87 kg) were significantly impacted by the rootstocks, with Dogridge rootstock recording the highest values. Additionally, 1103P resulted in longer shoot length (106.26 cm), number of canes (35.87), stock: scion ratio (0.96) and minimum days to achieve uniform colour (107.33 days) in Dogridge also led to the earliest harvest (139.80 days). Yield and quality parameters, including number of bunches vine-1 (31.80), 50 berry weight (159.78 g), yield vine-1 (8.52 kg), berry length (21.33 mm) and berry diameter (16.17 mm) were superior in vines grafted onto 1103P and Dogridge. Among quality attributes varied significantly, with 110R producing berries with the highest TSS (19.89 °Brix), while acidity was lowest in 140Ru (0.57%). This rootstock also recorded superior total chlorophyll content (19.10 mg ml-1) at 90 days after fruit pruning. For photosynthetic activity, 110R had the highest assimilation rate (7.67 µmol H2O m-2 s-1), while Dogridge showed superior stomatal conductance (0.18 µmol H2O m-2 s-1), intercellular CO2 (331.86 µmol CO2 mol-1), and transpiration rate (2.72 mmol H2O m-2 s-1). Overall, the findings suggest that both Dogridge and 1103P rootstocks significantly enhanced growth and yield, making it a suitable choice for Crimson Seedless grapevines in tropical conditions.